Tecnologia educativa para estudantes de enfermagem acerca da consulta de pré-natal de risco habitual - Mello, Giovana Batistella de (2024)
Introduction: Prenatal care is characterized by a set of routine consultations, whose central objective is to promote the development of a healthy pregnancy and a safe birth for the baby. With regard to maternal and child care, in prenatal care, in its guidelines and interventions, mainly in Primary Health Care (PHC), the professional nurse has a primary role, therefore, requires technical-scientific preparation to provide assistance. Objective: To build an educational technology for higher education nursing students about conducting prenatal consultations involving common risk in primary health care. Methodology: This is a methodological study for the construction of an educational guide, which will be guided by the stages of the ADDIE Model, of Instructional Design, in this study only stages A, D and D were developed. The first stage was the analysis of context, in which literature review studies, document readings and qualitative field research were carried out in order to determine knowledge gaps on the topic and the needs of the target audience (nursing students). Next, the Design and Development stages were carried out, where the educational guide was produced, with structuring of images, colors and characters. The project was approved by the Research Ethics Committee of the Federal University of Santa Maria, under opinion number 5.835.507 and CAAE 65543622.2.0000.5346. Results: The contents explored in the literature reviews revealed the need to construct TEs that consolidate and qualify the PN consultation during nursing graduation. The content from the WHO and MS highlights recommended and non-recommended practices for quality PN, consequently, for safe labor and birth. Field research, weaknesses present related to the beginning of the PN consultation and pertinent approaches in subsequent consultations. Also, it identified the contents that feel necessary to develop the PN consultation with greater autonomy and security. The construction of the guide had the support of the CTE, which was essential for better planning of information, illustrations and colors for the guide. Final considerations: It is seen that ET are facilitating, innovative and accessible tools, highly capable of intervening in the construction of theoretical-practical knowledge of nursing students, encouraging the break with the traditional teaching model and moving towards an innovative and creative model.